Abortion Act in Somerset. Issue 5871 (14th July 1973) - Jones, A. Parry; Grimoldby, M. R.
Abstract : A survey conducted with a sample of 20% of general practitioners over six months in 1972 disclosed a request rate for termination approaching 10% of all pregnancies. The attitude and performance of the practitioner were considered to be important in the patient's requests for this, and patients were thought to know about these. This implies that in three-quarters of the practices there was a sizeable demand for abortion which remained latent. Altogether, 20% of specialist consultations were made privately and in none of these cases was abortion refused. Under the Health Service the refusal rate was 19%, but 7 of the 12 women refused N.H.S. abortions subsequently obtained it privately.